Analisis persimpangan berlampu isyarat menggunakan highway capacity manual 1985 - Ismail Abd. Rahman, (1991)
This paper describes the control system's performance of a signalised intersection in Kajang town. Analysis which was carried out according to the method outlined in the Highway Capacity Manual 1985 (Hcm85) shows that a linear relationship between percentage of heavy vehicles in trafficflow to the approach's capacity exist in various control conditions. Besides that, this study also gives a relationship between delay experienced by any individual drivers to volume divided by capacity ratio (vle)